(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
This article of the author discusses the socio-cultural aspects of information security, it also says that the information security of society is to ensure the information interests of society as a whole. These interests include public information needs and interests, which in turn are aimed at ensuring the free exchange of information and interaction between various public institutions, organizations and citizens. The goal here is to ensure the information interests of society, public organizations and the interests of the individual in terms of their information rights. This includes freedom of access to information, the strengthening of real democracy, the development of a social and legal society, the maintenance of social harmony and the provision of social control.